Políticas públicas e a condição das pessoas com deficiência no sistema prisional: uma análise filosófica sobre direitos, exclusão e reconhecimento - Martins, Rebeca Gallo (Universidade Federal de São Carlos)
This study analyzes, from a Foucauldian and documentary perspective, public policies and the condition of persons with disabilities within the Brazilian prison system, emphasizing processes of exclusion, recognition, and biopolitics. Based on a bibliographic review and documentary analysis—including laws, decrees, institutional guidelines, official reports, and datasets from IBGE, INEP, RELIPEN, and SISDEPEN—the research is organized into three analytical axes: (1) the State, norms, and invisibilities; (2) data, structures, and exclusionary patterns in the prison context; and (3) anomalous bodies, biopolitics, and the management of the “undesirable.” The study reveals a significant gap between the normative framework (such as the Brazilian Inclusion Law, educational legislation, and accessibility standards) and institutional practice. Persistent shortcomings include insufficient accessible cells and adaptations, informational gaps, and the communicational invisibility of persons with disabilities. Official data also highlight structural deficits—such as the reduced number of adequate facilities compared to the population with disabilities—demonstrating systemic violations of rights. The research concludes that urgent actions are needed, including the production and standardization of specific data, the strengthening of intersectoral policies, effective implementation of accessibility measures, professional training, and enhanced monitoring by oversight bodies, to transform formal legal guarantees into concrete conditions of dignity and inclusion within prisons.
Public policies and the condition of persons with disabilities in the prison system: a philosophical analysis of rights, exclusion, and recognition.
Keywords: Sistema penitenciário; Política inclusiva; Acessibilidade; Educação especial; Biopoder; Penitentiary system; Inclusive policy; Accessibility; Biopower; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 10. Redução das Desigualdades; 4. Educação de Qualidade